BEL CERDAS CERMAT MENGGUNAKAN REMOTE CONTROL WIRELESS BERBASIS MIKROKONTROLER AT89S52 - Anggreni, Ni Luh Putu; Supardi, I Wayan; Wendri, Nyoman (BULETIN FISIKA, 2014)
successfully designed. AT89S52 microcontroller used to control the entire information system with seven segment display and ULN2003 serves as a current amplifier to activate the seven segment LED display compilers. The sensor are used is AT89S52 based wireless remote control with a maximum distance of the sensor placement that is sensor with a frequency of 27 MHz is 19 m and the sensor with a frequency of 49 MHz is 20 m, while for the sensor with a frequency of 27 MHz that is a sensor with a series of supporting circuit was 80.4 cm and the sensor with a frequency of 49 MHz is 90.4 cm.